1988
DOI: 10.1002/bjs.1800751206
|View full text |Cite
|
Sign up to set email alerts
|

Management of symptomatic gallstones in the elderly

Abstract: In a study of 544 patients with symptomatic gallstones 158 subjects were aged greater than 70 years. Elderly patients had a significantly higher incidence of emergency presentation, jaundice, cholangitis, ductal stones, biliary drainage procedures, and acute complications requiring urgent or emergency surgery (P less than 0.001); they had more than twice the incidence of postoperative complications in comparison with patients aged less than 70 years. There was an increased perioperative mortality in the elderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Reported overall mortality rates after LC in elderly patients vary from 0% to 1.6% [9, 10, 12, 22-25, 27-29, 41]. This is substantially less than the mortality reported after open cholecystectomy (OC) in elderly patients, which varies between 0.8% and 13% [16,18,19,38]. In our series, 186 patients underwent LC, of which 3 (1.6%) died.…”
Section: Discussionmentioning
confidence: 65%
“…Reported overall mortality rates after LC in elderly patients vary from 0% to 1.6% [9, 10, 12, 22-25, 27-29, 41]. This is substantially less than the mortality reported after open cholecystectomy (OC) in elderly patients, which varies between 0.8% and 13% [16,18,19,38]. In our series, 186 patients underwent LC, of which 3 (1.6%) died.…”
Section: Discussionmentioning
confidence: 65%
“…Institutional studies of unselected elderly patients undergoing LC have reported complication rates that range from 5% to 24% (average morbidity, 15%) and an overall mortality rate of 0.7% (range, 0-2%) [1,2,9,11,17,18,22,25,29]. This contrasts with reported complication rates of 11% to 62% (average morbidity, 26%) and an overall mortality of 6% in five different studies from the 1980s involving 719 open cholecystectomies [4,[13][14][15][16]19]. Furthermore, in Lujan et al's [17] prospective trial, complications occurred in 24% of the patients undergoing open cholecystectomy, as compared with 13.5% of the patients treated laparoscopically.…”
Section: Discussionmentioning
confidence: 99%
“…Census estimates suggest that the percentage of elderly persons in the United States will rise from 12.8% in 1995 to 16.5% over the next 25 years [30]. Although they currently comprise only one-eighth of the population, the elderly already account for nearly one-third of surgical patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The overall morbidity for endoscopic sphincterotomy/laparoscopic cholecystectomy is proportionately less, however, than that for open duct exploration in both the young and the elderly. 23 The results of laparoscopic duct exploration in non-specialist centres are unknown. The few series reporting laparoscopic duct exploration on selected patients from specialist centres suggest a higher complication rate than that achieved in this series using ERC/laparoscopic cholecystectomy.21 24 Thirdly, there is a perceived risk of more complications from endoscopic sphincterotomy in those with normal sized bile ducts.…”
Section: Discussionmentioning
confidence: 99%